172A research-policy partnership for the achieving the Sustainable Development Goals in Bangkok. (2nd September 2021) - Badland, Hannah; Alderton, Amanda; Higgs, Carl; Davern, Melanie; Butterworth, Iain; Correia, Joana; Nitvimol, Kornsupha
Abstract: Focus of presentation: Through the UN's Sustainable Development Goals (SDGs), there is a major commitment from cities to prioritise health and wellbeing, reduce poverty, support environmental resilience, and increase liveability. Existing tools for tracking progress towards liveable, equitable cities have been developed primarily for high-income country contexts. This project is a collaboration led by RMIT University (Australia), partnering with the Bangkok Metropolitan Administration (BMA) (Thailand), the UN Global Compact - Cities Programme, and the Victorian Department of Health and Human Services (Australia). It aims to provide a proof-of-concept spatial indicators system using open access and local spatial data to monitor progress towards the SDGs in Bangkok. Findings: Approximately 50 spatial indicators aligned to the SDGs have been generated for Bangkok. These are available in a range of formats, including a bi-lingual online-portal, and static and interactive maps. The BMA have identified three Bangkok districts for deeper interrogation, and on-going workshops shape the capacity building activities. Conclusions/Implications: This partnership has enhanced understandings of liveability within the SDG framework including: i) providing indicators for monitoring liveability in a low-to-middle income city context; ii) developing an international liveability network and deeper understanding of challenges; and iii) creating opportunities for capacity building and reciprocal learning. Key messages: There has been little 'liveability' guidance for cities in low- or middle-income country contexts. This project contributes to the global SDG agenda to enhance health and wellbeing through the built environment in diverse contexts.